Post-conflict reconstruction in Angola - Otitodun, Elizabeth (Department of Political Studies, 2019)
This study examined the main strategies adopted by the Angolan government in its post-conflict reconstruction efforts, and the extent to which these efforts have promoted durable peace in the country. The number of post-conflict countries on the continent is increasing, with 16 African countries already in the process of implementing peace agreements signed during the last decade. With research showing that up to 50 percent of post-conflict countries relapse into violent conflict within five to 10 years of signing a peace agreement, implementing practical and effective strategies to prevent a return to conflict becomes imperative. In the light of the limited experience of African countries in post-conflict situations, Angola presented an interesting case study. The oil and diamond rich country, emerging in 2002 from over 40 years of conflict, has been able to develop its own homegrown post-conflict reconstruction strategies. Notable progress in addressing some of its short-term post-conflict reconstruction priorities include, the successful resettlement of an estimated four million internally displaced persons (IDPs), and reintegrating more than half a million refugees and over 100 000 ex-combatants, into Angolan society. Progress in the areas of de-mining, as well as the rehabilitation of physical infrastructure, and increased enrolment in primary school education are other significant achievements. It is noteworthy that the Angolan government has, despite a lack of major international funding and overseas development assistance, been able to finance the majority of the expenses required for the country's reconstruction and re-Iaunching of the national economy. Importantly, the government's efforts have had some assistance in the form of oil-backed loans from China. Despite notable progress, such as the country's rapid economic growth, and being ranked 59th among the world's economies, Angola remains one of the most badly governed, corrupt, and unequal societies in the world. Credible improvements in the areas of good governance, socio-economic development, especially basic service delivery, and a more even distribution of the benefits of the country's oil wealth are vital in order to deliver significant peace dividends to the majority of the Angolan population. Making these improvements will be vital, and will influence considerably whether the country's post-conflict reconstruction efforts are ultimately successful.